Relationship between edaphic parameters and postharvest quality criteria of Prunus persica (L.) Batsch fruits by multivariate analysis (Scientia Agropecuaria, 2020)
This study was carried out in the main Escarcha variety peach producing area in the state of Tlaxcala, Mexico. Soil parameters were evaluated in plots with different management and some quality criteria in the fruit, to later relate them through a Principal Component Analysis (PCA). The results of the soil characterization evidenced a predominance of the sand fraction, low concentration of organic matter and total N, and few exchange sites. Yields of 10.88 to 11.66 t ha-1 were obtained. Through the PCA it was observed that the predictor variables in the case of the soil, in the main component one (CP1) were organic matter, organic carbon, total nitrogen and phosphorus; in CP2 were the apparent density, porosity, pH and the humification index. In the case of the fruit, in CP1 were weight, equatorial diameter, maturity index and number of fruits, and in CP2 were total titratable acidity and firmness. The PCA allowed identifying the soil variables that influence the quality of the fruit. The producer is recommended to increase the contents of organic matter, total N and P to obtain a greater number of fruits per tree and fruits with an adequate size, weight and maturity index in the evaluated plots. The post-harvest quality criteria showed that this variety is suitable for fresh consumption, for the preparation of preserves, compotes, jams and syrups; in addition to being classified as sweet, according to the maturity index.
Keywords: Soil properties; fruit growing; peach; postharvest; fruit quality.